A high-strength and high-toughness film and its preparation method and application
By using blending and composite technology of PBAT, PBS, polycaprolactone, starch-polylactic acid composite and cellulose nanocrystalline-polyhydroxy fatty acid ester composite in biofilm materials, the problem of insufficient strength and toughness of biofilm materials was solved, and a high-strength and high-strength film with excellent mechanical properties and good biodegradability was prepared.
Patent Information
- Application Number
- CN202411175464.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The existing biofilm materials have insufficient mechanical properties in terms of strength and toughness, making it difficult to effectively resist the risks of scratches and liquid leakage caused by external forces.
A high-strength and high-tough film composed of PBAT, PBS, polycaprolactone, starch-polylactic acid composite and cellulose nanocrystalline-polyhydroxy fatty acid ester composite is used to improve the tensile strength and toughness of the material through blending and composite technology.
It has achieved the preparation of high-strength and high-tough films, with excellent mechanical properties and good biodegradability, and can effectively resist external forces and quickly decompose in the natural environment.
Smart Images

Figure BDA0005010598690000181 
Figure BDA0005010598690000191
Abstract
Description
Technical Field
[0001] The present application relates to the field of new biological materials, and more specifically, to a high-strength and high-toughness film and a preparation method and application thereof. Background Art
[0002] With the rapid development of biotechnology, especially its wide application in pharmaceutical, cell culture and biomedical fields, the demand for biofilm materials is growing. In particular, disposable biofilm bags such as liquid storage bags, liquid preparation bags and cell reaction bags have become important consumables for biopharmaceutical companies in recent years.
[0003] Since biofilm bags have many requirements for comprehensive performance, they are usually made into multi-layer composite materials. For example, Chinese patent application publication number CN114434929A discloses a degradable film for disposable bags for biopharmaceuticals, which includes a protective layer, a high-component interlayer and a liquid contact layer. The liquid contact layer needs to have good biocompatibility to ensure that the drug is not contaminated during storage and transportation and maintains its original efficacy and safety. The high-component interlayer has excellent barrier properties and can effectively block the erosion of drugs by external factors such as oxygen and water vapor, thereby maintaining the stability and effectiveness of the drug.
[0004] However, whether it is the above-mentioned technology or other related disposable biofilm materials, the current research focus is mainly on biodegradability, while there is less research on its mechanical properties of strength and toughness. The film material should have sufficient strength to cope with the impact of external forces such as scratches on the integrity of the film. At the same time, the overall formula must have sufficient toughness to ensure that the risk of leakage will not be aggravated by bending during bag making and use.
[0005] Therefore, the preparation of film materials with high strength and high toughness is of great significance for the development of film bags for biopharmaceuticals. Summary of the invention
[0006] In order to prepare a film material with high strength and high toughness, the present application provides a high-strength and high-toughness film and a preparation method and application thereof.
[0007] In the first aspect, the present application provides a high-strength and high-toughness film, which adopts the following technical solution:
[0008] A high-strength and high-toughness film comprises a protective layer, a barrier layer and a liquid contact layer arranged in sequence from the outside to the inside, wherein the protective layer comprises the following raw materials in parts by weight:
[0009] 60-80 parts of PBAT, 20-35 parts of PBS, 18-30 parts of polycaprolactone, 10-20 parts of starch-polylactic acid complex, 8-15 parts of cellulose nanocrystal-polyhydroxyalkanoate complex.
[0010] By adopting the above technical scheme, in the present application, cellulose nanocrystals are added to the matrix material system of PBAT (polybutylene terephthalate-adipate) and PBS (polybutylene succinate). Cellulose nanocrystals are used as nanoscale fillers. Their high crystallinity and high strength characteristics enable the cellulose nanocrystals to form physical crosslinking points in the matrix material, restricting the movement of molecular chains, thereby improving the tensile strength and modulus of the material; and their surfaces are rich in active groups such as hydroxyl groups, which can form hydrogen bonds and other interactions with the matrix material, enhance the interfacial bonding force, and further improve the strength of the material; in addition, cellulose nanocrystals can form microcrack bridging and pull-out effects in the matrix material. When the material is subjected to external force, these effects can dissipate part of the energy, thereby delaying the expansion of cracks and improving the toughness of the material. The addition of cellulose nanocrystals in the protective layer can play a role in strengthening and toughening.
[0011] In the present application, polycaprolactone has good toughness and a long elongation at break. It can absorb more when the material is subjected to external force, thereby improving the toughness of the overall mixture. At the same time, polycaprolactone has certain similarities with the chemical structures of PBAT and PBS, which helps to improve the compatibility of the overall mixture, reduce phase separation, and further improve the mechanical properties of the overall mixture of the protective layer. In addition, polylactic acid itself has good strength, and starch particles play a role in dispersing stress in the mixture, reducing stress concentration. In addition, the addition of starch can also enhance the cohesion of the mixture by forming physical cross-linking points, further playing a reinforcing role. Cellulose nanocrystals form a strong network structure in the mixture, effectively transmit and disperse stress, improve the strength and rigidity of the material, and its nanoscale effect can significantly improve the toughness. A good composite structure is formed between the polyhydroxyalkanoate complex and the cellulose nanocrystals, further improving the overall performance of the mixture. Finally, the present application combines polycaprolactone, starch-polylactic acid complex, and cellulose nanocrystal-polyhydroxyalkanoate complex in the PBAT and PBS substrate system, which has excellent strength and excellent toughness.
[0012] In addition, PBAT, PBS, polycaprolactone, polylactic acid and polyhydroxyalkanoate complexes have good biodegradability and can be decomposed into harmless substances such as carbon dioxide and water by microorganisms in the natural environment. Starch, as a natural polymer material, not only increases the biodegradability of the mixture, but also is easily decomposed by microorganisms. The small molecules formed help microorganisms to further decompose other polymer materials and accelerate the degradation process of the entire mixture. The nanoscale effect of cellulose nanocrystals increases the specific surface area of the mixture, thereby promoting the attachment and degradation process of microorganisms to a certain extent. The final film has high strength and toughness while also having good biodegradability and is more environmentally friendly.
[0013] Optionally, the cellulose nanocrystal-polyhydroxyalkanoate composite is prepared by polymerizing itaconic acid, tert-butyl vinyl carbonate, and acrylate monomers to coat cellulose nanocrystals and then compounding with polyhydroxyalkanoate.
[0014] By adopting the above technical scheme, the addition of cellulose nanocrystals can play a role in strengthening and toughening. However, since cellulose nanocrystals are easy to crack and are easily affected by water, they are used as outer protective layer materials, which reduces the above-mentioned strengthening and toughening performance. Therefore, in this application, a film layer prepared by copolymerization of itaconic acid, tert-butyl vinyl carbonate and acrylate as monomers is coated on the cellulose nanocrystals. The addition of itaconic acid can improve the biodegradability of the acrylate copolymer, and itaconic acid can also chemically react with the hydroxyl groups in the cellulose nanocrystals to increase the esterification rate of the cellulose nanocrystals, thereby improving its compatibility with acrylates and the matrix materials of PBAT and PBS. In addition, the carboxyl functional groups in the polymer formed by copolymerization of itaconic acid, tert-butyl vinyl carbonate and acrylate through carbon-carbon unsaturated double bonds form chemical bonds with the cellulose nanocrystals, thereby achieving the polymer film layer on the cellulose nanocrystals. The directional polymerization coating on the cellulose nanocrystals; the addition of tert-butyl carbonate, in which the strong steric hindrance effect of the tert-butyl carbonate functional group significantly improves the susceptibility to water and thermal stability of cellulose nanocrystals, and the acrylate copolymer can further improve the toughening effect of cellulose nanocrystals, and improve the easy cracking performance of cellulose. Polyhydroxyalkanoic acid esters as polymer materials have good biodegradability and biocompatibility, and as polyester toughening, the surface of cellulose nanocrystals is coated with a polyacrylate polymer film layer and then composited with polyhydroxyalkanoic acid esters to improve the compatibility between cellulose nanocrystals and polyhydroxyalkanoic acid esters. The two cooperate with each other, and the hydrogen bond intermolecular force formed between cellulose nanocrystals and polyhydroxyalkanoic acid esters further enhances the interaction between the two phases, improves the easy cracking performance of cellulose nanocrystals, and finally significantly improves the strength and toughness of the film.
[0015] Optionally, the cellulose nanocrystal-polyhydroxyalkanoate composite is prepared by the following method:
[0016] 1) Add cellulose nanocrystals into ethanol, disperse them, then heat them to 70-75° C., then add an initiator, mix them, and prepare a first mixture;
[0017] 2) Mixing itaconic acid, versatate vinyl carbonate and acrylate monomers to prepare a monomer mixture;
[0018] 3) adding the monomer mixture in step 1) dropwise, reacting for 6-8 hours, then centrifuging, washing with alcohol, and freeze-drying to obtain primary cellulose nanocrystals;
[0019] 4) Dissolve polyhydroxyalkanoate in chloroform, raise the temperature to 45-55° C., then add the primary cellulose nanocrystals prepared in step 3), disperse by ultrasonication, and obtain a cellulose nanocrystal-polyhydroxyalkanoate complex after drying.
[0020] By adopting the above technical scheme, cellulose nanocrystals coated by copolymerization of acrylate, itaconic acid and tert-butyl vinyl carbonate are firstly prepared, and then compounded with polyhydroxyalkanoate to obtain a composite material.
[0021] Optionally, the acrylate monomer in step 2) is selected from one or more of methyl acrylate, ethyl acrylate, and butyl acrylate.
[0022] By adopting the above technical solution, the biodegradability is better when the above acrylate monomer is selected, especially the biodegradability of common methacrylate copolymers is poorer than that of methacrylate copolymers without methyl groups, so methacrylate monomers are selected in this application.
[0023] Optionally, when preparing a cellulose nanocrystal-polyhydroxyalkanoate composite, in step 1), the amount of ethanol added is 4-6 times the mass of the cellulose nanocrystal, and the amount of the initiator added is 1-3wt% of the amount of the monomer mixture added;
[0024] In step 2), the mass ratio of itaconic acid, versatate and acrylate monomers is 1:(1.2-1.5):(2-3), and the mass ratio of the monomer mixture to cellulose nanocrystals is 1:(0.6-0.8);
[0025] In step 4), the mass ratio of polyhydroxyalkanoate to chloroform is 1:(2-3), and the mass ratio of polyhydroxyalkanoate to primary cellulose nanocrystals is 1:(1.8-2.2).
[0026] By adopting the above technical solution and selecting the above ratio and addition amount, the cellulose nanocrystal-polyhydroxyalkanoate composite prepared has better toughening and strengthening effects and better biodegradability.
[0027] Optionally, the starch-polylactic acid composite is prepared by the following method:
[0028] Starch pretreatment: Add starch to dimethyl sulfoxide, heat to 60-70°C, then add maleic anhydride N,N-dimethylformamide solution, add peracetic acid, react for 1.5-2.5h, then neutralize and add ethanol to precipitate, wash and dry the precipitate to obtain pretreated starch;
[0029] Preparation of the composite: The prepared pretreated starch is then dissolved in dimethyl sulfoxide to form a starch solution, and then potassium tert-butoxide is added, the temperature is raised to 110-130°C, L-lactide is added after stirring, the reaction is carried out for 2-3 hours, and then the solution is cooled to room temperature and filtered and dried to obtain a starch-polylactic acid composite.
[0030] By adopting the above technical scheme, in the present application, the starch is first dissolved and then maleic anhydride is added for acylation treatment, and peracetic acid acts as a catalyst, and then neutralized and precipitated to obtain acylated starch, which can increase the lipophilicity of starch molecules, reduce the hydrogen bonding effect between starch molecules, and improve its compatibility with polylactic acid. The prepared starch-polylactic acid composite is more uniform, and it has better compatibility with other raw materials such as polycaprolactone, and the comprehensive performance of the final protective layer is better.
[0031] Optionally, when preparing the starch-polylactic acid composite, the mass ratio of starch to maleic anhydride is 1:(0.1-0.2), and the amount of peracetic acid added is 0.5-1.5wt% of the amount of starch added; the mass ratio of pretreated starch to L-lactide is 1:(0.8-1.2), and the amount of potassium tert-butoxide added is 1-3wt% of the pretreated starch.
[0032] By adopting the above technical solution, the starch-polylactic acid composite prepared by the above ratio is used for preparing the protective layer to obtain a film with better comprehensive performance.
[0033] Optionally, during the preparation of the starch-polylactic acid composite, when preparing the composite, after adding L-lactide and reacting for 1-1.5 hours, maleic anhydride grafted polypropylene is added, and the amount of maleic anhydride grafted polypropylene added is 3-5wt% of the pretreated starch.
[0034] By adopting the above technical scheme, the addition of maleic anhydride grafted polypropylene allows the polylactic acid chain segments formed after the ring-opening polymerization of L-lactide to form physical entanglement with the acylated starch and the maleic anhydride grafted polypropylene, and the carboxyl or hydroxyl functional groups on the polylactic acid chain segments are chemically cross-linked with the acyl groups in the acylated starch and the acyl groups in the maleic anhydride grafted polypropylene, thereby realizing the preparation of the final starch-polylactic acid composite. In addition, the formation of the above structure changes the molecular structure and crystallization properties of polylactic acid, thereby enhancing the interfacial bonding force between starch and polylactic acid, making the composite more cohesive, and further improving its toughening and strengthening effects.
[0035] In a second aspect, the present application provides a method for preparing a high-strength and high-toughness film, using the following technical solution:
[0036] A method for preparing a high-strength and high-toughness film comprises the following steps:
[0037] S1, mixing and homogenizing PBAT, PBS, polycaprolactone, starch-polylactic acid composite and cellulose nanocrystal-polyhydroxyalkanoate composite under vacuum, and then drawing and pelletizing in water to obtain a protective layer;
[0038] S2. The protective layer, the barrier layer and the liquid contact layer are processed through a multi-layer co-extrusion process to obtain a high-strength and high-toughness film.
[0039] By adopting the above technical solution, the method provided by the present application is simple and convenient and easy to realize industrialization.
[0040] In a third aspect, the present application provides an application of a high-strength and high-toughness film, using the following technical solution:
[0041] Application of a high-strength and high-toughness film in a biopharmaceutical film.
[0042] By adopting the above-mentioned technical scheme, the film prepared in the present application can be used in disposable bags or disposable bioreactors in biopharmaceuticals, has a good protective effect, and has sufficient strength to cope with the influence of external forces such as scratches on the integrity of the film. At the same time, the co-extruded film has sufficient toughness to ensure that the risk of leakage will not be aggravated by bending and the like during bag making and use.
[0043] In summary, this application has the following beneficial effects:
[0044] 1. In the present application, polycaprolactone has good toughness and a long elongation at break. It can absorb more when the material is subjected to external force, thereby improving the toughness of the overall mixture. At the same time, polycaprolactone has certain similarities with the chemical structures of PBAT and PBS, which helps to improve the compatibility of the overall mixture, reduce phase separation, and further improve the mechanical properties of the overall mixture of the protective layer. In addition, polylactic acid itself has good strength. Starch particles play a role in dispersing stress in the mixture, reducing stress concentration. The addition of starch can also enhance the cohesion of the mixture by forming physical crosslinking points, further playing a reinforcing role. Cellulose nanocrystals form a strong network structure in the mixture, effectively transmit and disperse stress, improve the strength and rigidity of the material, and its nanoscale effect can significantly improve toughness. A good composite structure is formed between the polyhydroxyalkanoate complex and the cellulose nanocrystals, further improving the overall performance of the mixture. Finally, the present application combines polycaprolactone, starch-polylactic acid complex, and cellulose nanocrystal-polyhydroxyalkanoate complex in the PBAT and PBS substrate system, which has excellent strength and excellent toughness.
[0045] 2. In the present application, the PBAT, PBS, polycaprolactone, polylactic acid and polyhydroxyalkanoate complexes have good biodegradability and can be decomposed into harmless substances such as carbon dioxide and water by microorganisms in the natural environment. Starch, as a natural polymer material, not only increases the biodegradability of the mixture, but also is easily decomposed by microorganisms. The small molecules formed help microorganisms to further decompose other polymer materials and accelerate the degradation process of the entire mixture. In addition, the nanoscale effect of cellulose nanocrystals increases the specific surface area of the mixture, thereby promoting the attachment and degradation process of microorganisms to a certain extent. The final film has high strength and toughness while also having good biodegradability. DETAILED DESCRIPTION
[0046] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0047] In the following examples and preparation examples, corn starch is used as starch, and maleic anhydride grafted polypropylene is maleic anhydride grafted polypropylene with a brand number of 900P and a product number of zj001 produced by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.;
[0048] Cellulose nanocrystals are cellulose nanocrystals from Huzhou Shansi New Material Technology Co., Ltd., which are prepared by hydrolyzing wood pulp with sulfuric acid to form nanorod-shaped cellulose crystals and spray-drying to obtain white powder;
[0049] The polyhydroxyalkanoate is selected from the polyhydroxyalkanoate of Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.
[0050] In the following embodiments, the liquid contact layer material is selected from linear low-density polyethylene LLDPE, specifically, the linear low-density polyethylene with the product number M2320 of Guangzhou Petrochemical;
[0051] The barrier layer is made of vinyl alcohol copolymer with the brand name Nichigo G-PolymerTMOKS-8095P.
[0052] Preparation Example 1
[0053] A method for preparing a cellulose nanocrystal-polyhydroxyalkanoate composite comprises the following steps:
[0054] 1) Using 1 kg of cellulose nanocrystals as a treatment basis, dissolving the cellulose nanocrystals in 5 times the mass of ethanol, ultrasonically dispersing for 25 minutes, then heating to 70° C., then adding initiator dibenzoyl peroxide, mixing, and obtaining a first mixture;
[0055] 2) Itaconic acid, versatate vinyl ester and butyl acrylate monomers are mixed in a mass ratio of 1:1.3:2.5 to prepare a monomer mixture, and the mass ratio of the monomer mixture to the cellulose nanocrystals is 1:0.7, and the amount of the initiator added is 2wt% of the amount of the monomer mixture added;
[0056] 3) adding the monomer mixture prepared in step 2) dropwise into step 1), reacting for 7 hours, then centrifuging, washing with alcohol, and freeze-drying to obtain primary cellulose nanocrystals;
[0057] 4) Dissolve polyhydroxyalkanoate in chloroform, and the mass ratio of polyhydroxyalkanoate to chloroform is 1:2.5, heat to 50°C, then add the primary cellulose nanocrystals prepared in step 3), the mass ratio of polyhydroxyalkanoate to primary cellulose nanocrystals is 1:2, ultrasonically disperse for 25 minutes, and obtain a cellulose nanocrystal-polyhydroxyalkanoate composite after drying.
[0058] Preparation Example 2
[0059] A method for preparing a cellulose nanocrystal-polyhydroxyalkanoate composite comprises the following steps:
[0060] 1) Using 1 kg of cellulose nanocrystals as a treatment basis, dissolving the cellulose nanocrystals in 4 times the mass of ethanol, ultrasonically dispersing for 20 minutes, then heating to 70° C., then adding initiator dibenzoyl peroxide, mixing, and obtaining a first mixture;
[0061] 2) Itaconic acid, versatate vinyl ester and butyl acrylate monomers are mixed in a mass ratio of 1:1.2:2 to prepare a monomer mixture, and the mass ratio of the monomer mixture to the cellulose nanocrystals is 1:0.6, and the amount of the initiator added is 1wt% of the amount of the monomer mixture added;
[0062] 3) adding the monomer mixture prepared in step 2) dropwise into step 1), reacting for 6 hours, then centrifuging, washing with alcohol, and freeze-drying to obtain primary cellulose nanocrystals;
[0063] 4) Dissolve polyhydroxyalkanoate in chloroform, and the mass ratio of polyhydroxyalkanoate to chloroform is 1:2, heat to 45°C, then add the primary cellulose nanocrystals prepared in step 3), the mass ratio of polyhydroxyalkanoate to primary cellulose nanocrystals is 1:1.8, ultrasonically disperse for 20 minutes, and obtain a cellulose nanocrystal-polyhydroxyalkanoate composite after drying.
[0064] Preparation Example 3
[0065] A method for preparing a cellulose nanocrystal-polyhydroxyalkanoate composite comprises the following steps:
[0066] 1) Using 1 kg of cellulose nanocrystals as a treatment basis, dissolving the cellulose nanocrystals in 6 times the mass of ethanol, ultrasonically dispersing for 30 minutes, then heating to 75° C., then adding initiator dibenzoyl peroxide, mixing, and obtaining a first mixture;
[0067] 2) Itaconic acid, tert-butyl carbonate and butyl acrylate monomers are mixed in a mass ratio of 1:1.5:3 to prepare a monomer mixture, and the mass ratio of the monomer mixture to cellulose nanocrystals is 1:0.8, and the amount of initiator added is 3wt% of the amount of the monomer mixture added;
[0068] 3) adding the monomer mixture prepared in step 2) dropwise into step 1), reacting for 8 hours, then centrifuging, washing with alcohol, and freeze-drying to obtain primary cellulose nanocrystals;
[0069] 4) Dissolve polyhydroxyalkanoate in chloroform, and the mass ratio of polyhydroxyalkanoate to chloroform is 1:3, heat to 45-55°C, then add the primary cellulose nanocrystals prepared in step 3), the mass ratio of polyhydroxyalkanoate to primary cellulose nanocrystals is 1:2.2, ultrasonically disperse for 30 minutes, and obtain a cellulose nanocrystal-polyhydroxyalkanoate composite after drying.
[0070] Preparation Example 4
[0071] A method for preparing a cellulose nanocrystal-polyhydroxyalkanoate composite is carried out according to the method in Preparation Example 1, except that in step 2), an equal amount of tert-butyl carbonate is replaced by butyl acrylate.
[0072] Comparative Preparation Example 1
[0073] A method for preparing a cellulose nanocrystal-polyhydroxyalkanoate composite is carried out according to the method in Preparation Example 1, except that in step 4), an equal amount of polyhydroxyalkanoate is replaced by polylactic acid.
[0074] Preparation Example 5
[0075] A method for preparing a starch-polylactic acid composite comprises the following steps:
[0076] Starch pretreatment: 1 kg of starch is used as the treatment basis, starch is added to dimethyl sulfoxide, heated to 65°C, and then maleic anhydride N, N-dimethylformamide solution is added, and peracetic acid is added, reacted for 2 hours, and then ethanol is added after neutralization to precipitate, and the precipitate is washed and dried to obtain pretreated starch;
[0077] The added mass ratio of starch to maleic anhydride is 1:0.15, the added amount of N,N-dimethylformamide is 3 times the mass of maleic anhydride, the added amount of dimethyl sulfoxide is 4 times the mass of starch, and the added amount of peracetic acid is 1wt% of the added amount of starch;
[0078] Preparation of the composite: The prepared pretreated starch is then dissolved in dimethyl sulfoxide to form a starch solution, and then potassium tert-butoxide is added, the temperature is raised to 120°C, L-lactide is added after stirring, the reaction is carried out for 2.5 hours, and then the solution is cooled to room temperature and filtered and dried to obtain a starch-polylactic acid composite.
[0079] During the preparation of the above-mentioned composite, the addition mass ratio of pretreated starch to L-lactide is 1:1, and the addition amount of potassium tert-butoxide is 2wt% of the pretreated starch, and the addition amount of dimethyl sulfoxide is 5 times the mass of the pretreated starch.
[0080] Preparation Example 6
[0081] A method for preparing a starch-polylactic acid composite comprises the following steps:
[0082] Starch pretreatment: 1 kg of starch is used as the treatment basis, starch is added to dimethyl sulfoxide, heated to 60°C, and then maleic anhydride N, N-dimethylformamide solution is added, and peracetic acid is added, reacted for 2.5 hours, and then ethanol is added after neutralization to precipitate, and the precipitate is washed and dried to obtain pretreated starch;
[0083] The added mass ratio of starch to maleic anhydride is 1:0.1, the added amount of N,N-dimethylformamide is 2 times the mass of maleic anhydride, the added amount of dimethyl sulfoxide is 3 times the mass of starch, and the added amount of peracetic acid is 0.5wt% of the added amount of starch;
[0084] Preparation of the composite: The prepared pretreated starch is then dissolved in dimethyl sulfoxide to form a starch solution, and then potassium tert-butoxide is added, the temperature is raised to 110°C, L-lactide is added after stirring, the reaction is carried out for 3 hours, and then the solution is cooled to room temperature and filtered and dried to obtain a starch-polylactic acid composite.
[0085] During the preparation of the above-mentioned composite, the added mass ratio of pretreated starch to L-lactide was 1:0.8, and the added amount of potassium tert-butoxide was 1wt% of the pretreated starch, and the added amount of dimethyl sulfoxide was 4 times the mass of the pretreated starch.
[0086] Preparation Example 7
[0087] A method for preparing a starch-polylactic acid composite comprises the following steps:
[0088] Starch pretreatment: 1 kg of starch is used as the treatment basis, starch is added to dimethyl sulfoxide, heated to 70°C, and then maleic anhydride N, N-dimethylformamide solution is added, and peracetic acid is added, reacted for 1.5 hours, and then ethanol is added after neutralization to precipitate, and the precipitate is washed and dried to obtain pretreated starch;
[0089] The added mass ratio of starch to maleic anhydride is 1:0.2, the added amount of N,N-dimethylformamide is 4 times the mass of maleic anhydride, the added amount of dimethyl sulfoxide is 5 times the mass of starch, and the added amount of peracetic acid is 1.5wt% of the added amount of starch;
[0090] Preparation of the composite: The prepared pretreated starch is then dissolved in dimethyl sulfoxide to form a starch solution, and then potassium tert-butoxide is added, the temperature is raised to 130°C, L-lactide is added after stirring, the reaction is carried out for 2 hours, and then the solution is cooled to room temperature and filtered and dried to obtain a starch-polylactic acid composite.
[0091] During the preparation of the above-mentioned composite, the added mass ratio of pretreated starch to L-lactide was 1:1.2, and the added amount of potassium tert-butoxide was 3wt% of the pretreated starch, and the added amount of dimethyl sulfoxide was 6 times the mass of the pretreated starch.
[0092] Preparation Example 8
[0093] A method for preparing a starch-polylactic acid composite is carried out according to the method in Preparation Example 5, except that, when preparing the composite, maleic anhydride grafted polypropylene is added after L-lactide is added and reacted for 1.5 hours, and then the reaction is continued for 1 hour, and the amount of maleic anhydride grafted polypropylene added is 4wt% of the pretreated starch.
[0094] Preparation Example 9
[0095] A method for preparing a starch-polylactic acid composite is carried out according to the method in Preparation Example 5, except that, when preparing the composite, maleic anhydride grafted polypropylene is added after L-lactide is added and reacted for 1 hour, and then the reaction is continued for 1 hour, and the amount of maleic anhydride grafted polypropylene added is 3wt% of the pretreated starch.
[0096] Preparation Example 10
[0097] A method for preparing a starch-polylactic acid composite is carried out according to the method in Preparation Example 5, except that when preparing the composite, after adding L-lactide and reacting for h, maleic anhydride grafted polypropylene is added, and then the reaction is continued for 1 h, and the amount of maleic anhydride grafted polypropylene added is 5wt% of the pretreated starch.
[0098] Preparation Example 11
[0099] A method for preparing a starch-polylactic acid composite is carried out according to the method in Preparation Example 5, except that the starch is not pretreated and is directly dissolved in dimethyl sulfoxide for the composite preparation step.
[0100] Example 1
[0101] A method for preparing a high-strength and high-toughness film comprises the following steps:
[0102] S1, 70kg PBAT, 28kg PBS, 22kg polycaprolactone, 15kg starch-polylactic acid composite prepared in Preparation Example 5 and 10kg cellulose nanocrystal-polyhydroxyalkanoate composite prepared in Preparation Example 1 were mixed and homogenized under vacuum, and then stretched and pelletized in 8°C water to obtain a protective layer raw material;
[0103] Using vinyl alcohol copolymer as the barrier layer raw material;
[0104] Linear low-density polyethylene LLDPE is used as the raw material of the liquid contact layer;
[0105] A tackifying resin is provided between the protective layer and the barrier layer, and a tackifying resin is also provided between the barrier layer and the liquid contact layer. The tackifying resin is a tackifying resin of the brand BTR8002P.
[0106] S2. Add the raw materials for the protective layer, the tackifying resin, the raw materials for the barrier layer, the tackifying resin and the raw materials for the liquid contact layer into the corresponding feed channels of the multi-layer co-extrusion film blowing machine respectively according to the sequence, blow the film after melting and then extend the multi-layer film out, and then cool, wind up and cut to obtain a high-strength and high-toughness film, and the obtained high-strength and high-toughness film comprises a protective layer, a barrier layer and a liquid contact layer from the outside to the inside, a tackifying resin layer is formed between the protective layer and the barrier layer, and a tackifying resin layer is also formed between the barrier layer and the liquid contact layer, the thickness of the protective layer is 20μm, the thickness of the barrier layer is 20μm, the thickness of the liquid contact layer is 200μm, and the thickness of the tackifying resin layer is 10μm.
[0107] Example 2
[0108] A method for preparing a high-strength and high-toughness film comprises the following steps:
[0109] S1, 60kg PBAT, 20kg PBS, 18kg polycaprolactone, 10kg starch-polylactic acid composite prepared in Preparation Example 6 and 8kg cellulose nanocrystal-polyhydroxyalkanoate composite prepared in Preparation Example 2 were mixed and homogenized under vacuum, and then stretched and pelletized in 5°C water to obtain a protective layer raw material;
[0110] Using vinyl alcohol copolymer as the barrier layer raw material;
[0111] Linear low-density polyethylene LLDPE is used as the raw material of the liquid contact layer;
[0112] A tackifying resin is provided between the protective layer and the barrier layer, and a tackifying resin is also provided between the barrier layer and the liquid contact layer. The tackifying resin is a tackifying resin of the brand BTR8002P.
[0113] S2. Add the raw materials for the protective layer, the tackifying resin, the raw materials for the barrier layer, the tackifying resin and the raw materials for the liquid contact layer into the corresponding feed channels of the multi-layer co-extrusion film blowing machine respectively according to the sequence, blow the film after melting and then extend the multi-layer film out, and then cool, wind up and cut to obtain a high-strength and high-toughness film, and the obtained high-strength and high-toughness film comprises a protective layer, a barrier layer and a liquid contact layer from the outside to the inside, a tackifying resin layer is formed between the protective layer and the barrier layer, and a tackifying resin layer is also formed between the barrier layer and the liquid contact layer, the thickness of the protective layer is 20μm, the thickness of the barrier layer is 20μm, the thickness of the liquid contact layer is 200μm, and the thickness of the tackifying resin layer is 10μm.
[0114] Example 3
[0115] A method for preparing a high-strength and high-toughness film comprises the following steps:
[0116] S1, 80kg PBAT, 35kg PBS, 30kg polycaprolactone, 20kg starch-polylactic acid composite prepared in Preparation Example 7 and 15kg cellulose nanocrystal-polyhydroxyalkanoate composite prepared in Preparation Example 3 were mixed and homogenized under vacuum, and then stretched and pelletized in water at 10°C to obtain a protective layer raw material;
[0117] Using vinyl alcohol copolymer as the barrier layer raw material;
[0118] Linear low-density polyethylene LLDPE is used as the raw material of the liquid contact layer;
[0119] A tackifying resin is provided between the protective layer and the barrier layer, and a tackifying resin is also provided between the barrier layer and the liquid contact layer. The tackifying resin is a tackifying resin of the brand BTR8002P.
[0120] S2. Add the raw materials for the protective layer, the tackifying resin, the raw materials for the barrier layer, the tackifying resin and the raw materials for the liquid contact layer into the corresponding feed channels of the multi-layer co-extrusion film blowing machine respectively according to the sequence, blow the film after melting and then extend the multi-layer film out, and then cool, wind up and cut to obtain a high-strength and high-toughness film, and the obtained high-strength and high-toughness film comprises a protective layer, a barrier layer and a liquid contact layer from the outside to the inside, a tackifying resin layer is formed between the protective layer and the barrier layer, and a tackifying resin layer is also formed between the barrier layer and the liquid contact layer, the thickness of the protective layer is 20μm, the thickness of the barrier layer is 20μm, the thickness of the liquid contact layer is 200μm, and the thickness of the tackifying resin layer is 10μm.
[0121] Embodiment 4-7
[0122] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that the starch-polylactic acid composite is the starch-polylactic acid composite prepared in Preparation Examples 8-11 respectively.
[0123] Example 8
[0124] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that the cellulose nanocrystal-polyhydroxyalkanoate composite is the cellulose nanocrystal-polyhydroxyalkanoate composite prepared in Preparation Example 4.
[0125] Comparative Example 1
[0126] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that the cellulose nanocrystal-polyhydroxyalkanoate composite in step S1 is the cellulose nanocrystal-polyhydroxyalkanoate composite prepared in Comparative Preparation Example 1.
[0127] Comparative Example 2
[0128] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that the cellulose nanocrystal-polyhydroxyalkanoate complex in step S1 is replaced by cellulose nanocrystals in equal amounts.
[0129] Comparative Example 3
[0130] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that no cellulose nanocrystal-polyhydroxyalkanoate complex is added in step S1.
[0131] Comparative Example 4
[0132] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that in step S1, the cellulose nanocrystal-polyhydroxyalkanoate complex is replaced by an equal amount of a mixture of polyhydroxyalkanoate and cellulose nanocrystals, and the mass ratio of polyhydroxyalkanoate to cellulose nanocrystals is 1:2.
[0133] Comparative Example 5
[0134] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that polycaprolactone is not added in step S1.
[0135] Comparative Example 6
[0136] A method for preparing a high-strength and high-toughness film is carried out according to the method in Example 1, except that the cellulose nanocrystal-polyhydroxyalkanoate composite is replaced by polyhydroxyalkanoate in equal amounts.
[0137] Performance Testing
[0138] The degradation rate, tensile strength and elongation at break of the films prepared in the examples and comparative examples of the present application were tested, wherein the degradation rate was tested in accordance with GB / T 19277.1-2011, and the tensile strength and elongation at break were tested in accordance with ASTM D882. The test results are shown in Table 1 below.
[0139] Table 1:
[0140]
[0141]
[0142] Referring to the test results in Table 1 above, the film prepared in the embodiment of the present application has excellent mechanical properties and excellent biodegradability. Referring to the test results of Example 1 and Examples 4-6, it can be seen that when the starch-polylactic acid composite is prepared and maleic anhydride grafted polypropylene is added in the subsequent treatment, although the biodegradability is slightly reduced compared with Example 1, the mechanical properties of the film can be significantly improved due to the entangled structure formed by the three. In addition, maleic anhydride grafted polypropylene improves the compatibility between starch and polylactic acid, and the formed phase chemical bonding improves the tensile strength of the overall material. In addition, maleic anhydride grafted acrylic acid The long-chain branched structure is introduced, and physical crosslinking is formed between polylactic acid and starch, which significantly improves the elongation at break, and the film finally obtained has high tensile strength and high elongation at break; combined with the test results of Example 7, it can be seen that when the starch is directly compounded with the polylactic acid precursor to obtain a composite material without being treated, its mechanical properties are reduced; combined with the test results of Example 8, when the cellulose nanocrystal-polyhydroxyalkanoate composite is prepared, when versatile vinyl carbonate is not added to the monomer solution, the mechanical properties of the obtained film are also reduced. This is mainly because the cellulose nanocrystals are easily affected by water, resulting in a decrease in their mechanical properties.
[0143] Referring to the test results in Example 1 and Comparative Example 1, when the cellulose nanocrystal-polyhydroxyalkanoate composite was replaced by the cellulose nanocrystal-polylactic acid composite in equal amounts in Comparative Example 1, its mechanical properties were significantly reduced. Combined with the test results in Comparative Example 4, the cellulose nanocrystals were directly mixed with the polyhydroxyalkanoate and then added without passing through the acrylic film layer to form the final film. The mechanical properties were also significantly reduced. Combined with the test results in Comparative Example 2, when only cellulose nanocrystals were added to the film, the elongation at break was significantly reduced. This is mainly because the cellulose nanocrystals showed a certain brittleness, so their surface was first acrylated. The cellulose ester polymer is coated to achieve a toughening effect, and the toughening effect of polyhydroxyalkanoate is combined to achieve an enhanced toughening effect. Referring to the test results of Example 1 and Comparative Example 3, when the cellulose nanocrystal-polyhydroxyalkanoate composite is not added in step S1, the mechanical properties of the film are weak, and the biodegradability is also reduced. Combined with the test results of Comparative Example 5, when polycaprolactone is not added to the film raw material, the elongation at break is significantly reduced, and the toughness is reduced. Combined with the test results of Comparative Example 6, when only polyhydroxyalkanoate is added, the strength performance is low, and the biodegradability is also significantly reduced.
[0144] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength and high-toughness film, comprising a protective layer, a barrier layer and a liquid contact layer arranged in sequence from the outside to the inside, characterized in that: The protective layer comprises the following raw materials in parts by weight: 60-80 parts of PBAT, 20-35 parts of PBS, 18-30 parts of polycaprolactone, 10-20 parts of starch-polylactic acid complex, 8-15 parts of cellulose nanocrystal-polyhydroxyalkanoate complex; The cellulose nanocrystal-polyhydroxyalkanoate composite is prepared by the following method: 1) Add cellulose nanocrystals into ethanol, disperse them, then heat them to 70-75° C., then add an initiator, mix them, and prepare a first mixture; 2) Mixing itaconic acid, versatate vinyl carbonate and acrylate monomers to prepare a monomer mixture; 3) In step 1), the monomer mixture is added dropwise, reacted for 6-8 hours, then centrifuged, washed with alcohol, and freeze-dried to obtain primary cellulose nanocrystals; 4) dissolving polyhydroxyalkanoate in chloroform, heating to 45-55° C., then adding the primary cellulose nanocrystals prepared in step 3), dispersing by ultrasonication, and obtaining a cellulose nanocrystal-polyhydroxyalkanoate composite after drying; The starch-polylactic acid composite was prepared by the following method: Starch pretreatment: Add starch to dimethyl sulfoxide, heat to 60-70°C, then add maleic anhydride N,N-dimethylformamide solution, add peracetic acid, react for 1.5-2.5h, then neutralize and add ethanol to precipitate, wash and dry the precipitate to obtain pretreated starch; Preparation of the composite: the prepared pretreated starch is then dissolved in dimethyl sulfoxide to form a starch solution, and then potassium tert-butoxide is added, the temperature is raised to 110-130°C, L-lactide is added after stirring, the reaction is carried out for 2-3 hours, and then the solution is cooled to room temperature and filtered and dried to obtain a starch-polylactic acid composite; When preparing the cellulose nanocrystal-polyhydroxyalkanoate composite, in step 1), the amount of ethanol added is 4-6 times the mass of the cellulose nanocrystal, and the amount of initiator added is 1-3wt% of the amount of the monomer mixture added; In step 2), the mass ratio of itaconic acid, versatate and acrylate monomers is 1:(1.2-1.5):(2-3), and the mass ratio of the monomer mixture to cellulose nanocrystals is 1:(0.6-0.8); In step 4), the mass ratio of polyhydroxyalkanoate to chloroform is 1:(2-3), and the mass ratio of polyhydroxyalkanoate to primary cellulose nanocrystals is 1:(1.8-2.2); When preparing the starch-polylactic acid composite, the added mass ratio of starch to maleic anhydride is 1: (0.1-0.2), and the added amount of peracetic acid is 0.5-1.5wt% of the added amount of starch; the added mass ratio of pretreated starch to L-lactide is 1: (0.8-1.2), and the added amount of potassium tert-butoxide is 1-3wt% of the pretreated starch; During the preparation of the starch-polylactic acid composite, when preparing the composite, after adding L-lactide and reacting for 1-1.5 hours, maleic anhydride grafted polypropylene is added, and the amount of maleic anhydride grafted polypropylene added is 3-5wt% of the pretreated starch.
2. A high-strength and high-toughness film according to claim 1, characterized in that: The acrylic acid ester monomer in step 2) is selected from one or more of methyl acrylate, ethyl acrylate and butyl acrylate.
3. The method for preparing a high-strength and high-toughness film according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, mixing and homogenizing PBAT, PBS, polycaprolactone, starch-polylactic acid composite and cellulose nanocrystal-polyhydroxyalkanoate composite under vacuum, and then drawing and pelletizing in water to obtain a protective layer; S2. The protective layer, the barrier layer and the liquid contact layer are processed through a multi-layer co-extrusion process to obtain a high-strength and high-toughness film.
4. Use of the high-strength and high-toughness film as claimed in any one of claims 1 to 2 in disposable bags or disposable bioreactors for biopharmaceuticals.
Citation Information
Patent Citations
Degradable film of disposable bag for biopharmacy and application of degradable film
CN114434929A
Full-degradable plastic processing technology
CN114702798A